Hellenistic mouldmade relief bowls in Thessaly - Dalgkitsi, A (2023)
This thesis offers the first comprehensive and comparative study of Hellenistic mouldmade relief bowls discovered in Thessaly. The material under examination originates from old (1906-1916) and more recent excavations (1970s – to this day) across 23 Thessalian sites, conducted under the auspices of the Archaeological Society of Athens (under A. Arvanitopoulos) and the local Ephorates of Antiquities. Out of the 616 complete and fragmentary bowls examined here (which are recorded in 568 catalogue entries), only a few groups have been partially published to this day.